VILLAGE FUND MANAGEMENT PHENOMENOLOGICAL STUDY IN WERE VILLAGE, CENTRAL HALMAHERA REGENCY - Noho, Adisa; Jeandry, Gregorius; Suwito, Suwito; Ali, Iqbal M Aris (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This study aims to determine the phenomenon that occurs as well as community perceptions about the process of managing village funds in Were Village regarding the planning, implementation and accountability of village funds in Were Village, Weda District, Central Halmahera Regency. The research method used in this study is a qualitative phenomenological approach, where in this research it is descriptive, namely looking in detail at the phenomena that are really visible. The results of this study show that the management of village funds in Were Village is quite good. The village apparatus has tried to realize community welfare despite the lack of communication, causing the implementation of its management to involve only a few village communities. Community participation is very minimal due to miscommunication between village officials to the community, this is due to the lack of socialization from village officials so that the understanding of the people of Were Village itself lacks understanding of village fund management in Were Village. Therefore, it is hoped that the village can jointly increase self-awareness and be more open about the management of village funds in the village itself.